IMPLEMENTATION OF THE MANAGEMENT POLICY OF CISANGKAL TOURISM VILLAGE BANGUNKARYA VILLAGE LANGKAPLANCAR DISTRICT PANGANDARAN REGENCY - Ahmad Fauzi; Ii Sujai; Candra Firmanto (JGSRD: Journal of Government Science and Rural Development, 2023)
This study aims to determine the extent of policy implementation in tourism management, especially in the Cisangkal tourism village program in Bangunkarya Village, Pangandaran Regency. The problem is that the facilities and infrastructure are not complete, such as the absence of an information board regarding the existence of the Cisangkal Tourism Village, Bangunkarya Village. The level of public awareness to be involved in activities in the Cisangkal tourist village is still low, the lack of socialization carried out by the Bangunkarya Village Government, Langkaplancar District, Pangandaran Regency to the people of the village area so that there are still people who do not know the community-based tourism village program. Therefore, this study focuses on the implementation of policies in tourism management, especially in the Cisangkal tourist village program in Bangunkarya Village, Pangandaran Regency. The method used in this study, using a qualitative descriptive method. The data and data sources used are primary and secondary data with data collection techniques, namely interviews, observation and documentation and using data analysis techniques, namely data reduction, data presentation, and conclusions and verification. The results of this study indicate that the level of policy implementation for the management of the Cisangkal tourist village has not been optimal. From this study, that the importance of implementing policies in tourism management, especially in the Cisangkal tourist village program in Bangunkarya Village, Pangandaran Regency, is related to the development of village tourism for the future.